PROFESSIONAL EXAMINATIONS. (The Accounting Review, 1930)
Abstract Certified Public Accountants (C.P.A.) examinations have long been accepted as phenomena of the first importance in the academic apprenticeship of the accountant. At one time, so far removed from each other were the training for and the practice of the profession that the skilled practitioner was regarded with no little awe in academic byways. He was a moving and dynamic figure, the paragon of the accounting world, and perhaps rightfully so; for was he not a master of an amazing technique, a technique evidenced by artfully designed C.P.A. problems? He had produced no other literature. His creations were pounced upon as manna for classroom consumption; and many were the threads to be spun about their engrossing obscurities. C.P.A. problems were the first footbridge between theory and practice, or, more accurately, between the theories of textbooks and the theories of practitioners. The American Institute of Accountants has been in a unique position during the past thirteen years in framing a uniform examination for more than thirty states.